Metal organic chemical vapor deposition of m-plane GaN epi-layer using a three-step approach towards enhanced surface morphology - Azman, Adreen; Shuhaimi, Ahmad; Omar, Al-Zuhairi; Kamarundzaman, Anas; Abdul Khudus, Muhammad Imran Mustafa; Ariff, Azharul; Samsudin, M.E.A.; Zainal, Norzaini; Rahman, Saadah Abdul (Elsevier, 2018)
Specular m-plane (101¯0) gallium nitride (m-GaN) epi-layer are grown on m-plane (101¯0) sapphire substrates by metal organic chemical vapor deposition using a three-step approach. A two-step approach was used to grow m-GaN buffer layer (BL), while a three-step approach was applied to improve the surface morphology of the top m-GaN epi-layer at high temperature. The three-step approach started with growing m-aluminum nitride nucleation layer with an optimized ammonia flux during the growth of aluminum nitride. Then the temperature was ramped up during the recrystallization step before the m-GaN BL deposition at low-temperature and the growth of m-GaN layer at high-temperature for the final step. Unexpectedly, when ammonia flow was intentionally halted during the recrystallization step, the surface morphology of the BL drastically changed from three- to two- dimensional with an abrupt cross-sectional structure. This in turn facilitated the complete coalescence of the m-GaN layer as revealed by field emission scanning electron microscopy. The three-step technique was found to affect the quality of m-GaN epi-layer as the samples exhibit improved crystallinity with X-ray diffraction rocking curves widths of 4680 and 1980 arcsec along the azimuth, perpendicular and parallel to [101¯0] directions, respectively.